DETERMINING AND DIAGNOSING AFFLICTIONS AND DISEASES IN THE NOBLE QUR’AN - Ruaa Mhmood Shihab; Mohammed Khalil Khairullah (American Journals Publishing, 2022)
To test in language is a test and a test, Ibn Manzur said: “A man has been afflicted with calamity and calamity, and I have afflicted him: I have tested him…, and calamity is in good and evil, it is said: I have afflicted him with a good trial and a bad calamity. There is not much difference between the idiomatic meaning and the linguistic meaning.
Keywords: diagnosing; afflictions,; Noble Qur’an